The Digital Life Narrative of a Romanian Transgender Microcelebrity through the Lens of Networked Publics - Alexandra Cotoc; Anamaria Radu (European Journal of Life Writing, 2025)
This contribution investigates the online identity construction of the Romanian transgender vlogger Daria Jane, using as subjects of analysis her YouTube digital diary as well as videos published on the YouTube channel of a famous Romanian TV presenter who invited Daria to tell her transitioning story. Specifically, we will analyse viewers’ reactions in the comments sections of two videos, exploring the interplay between biography and autobiography within the digital space in the process. Using an interdisciplinary methodological framework that integrates online discourse analysis, identity studies, (micro)celebrity studies, and (auto)biography research, the paper addresses the ways in which Netizens co-construct Daria Jane’s life story on social media. Our methodology consists of examining a corpus of comments, identifying keywords, and creating categories (negative stancetaking and positive stancetaking) that reflect the attitudes and positions of Romanian users towards transgender identities. The study contributes to the scholarly discourse on online  (self-)presentation by offering an analysis of YouTube comments and a visualisation of the data derived from these comments via the categories created. Furthermore, by exploring the dynamic relationships between Daria Jane, the TV host, and Romanian YouTube users, the article sheds light on the Romanian public perception regarding (trans)gender identities.